Impact of social media and user- generated content on travellers for vacation decision-making. - Khara, Priyal (2012)
Everyone takes holidays for a break from their busy schedule and spend time with their closed ones. Holidays are a relief from stressful and the hectic life, giving time for recovery and rest in the pleasant companionship of the family and friends, and in todays time it has turned to be a challenge as it is a huge expense, combining needs and fulfilling wishes of the different members of the family: parents and children, mothers and fathers, young children and older children. Family holidays just involve a little stress to experience wonderful and memorable moments. Some family holidays – or at least some situations in family holidays – are perceived as successful and just the way they were supposed to be because of the right decision made which involves various aspect from recognizing the problem, doing complete information research and selecting the best alternative. Today it is about the right kind of information collected that leads to these “good experiences” and “good moments” This study investigates the impact of information received through internet specifically social media, user generated content and the search engine on vacation decision making. The study is carried out with the support of literature related to vacation decision-making and the growing importance of social media and blogs as an information source for the same and the various factors that affect this process. Research is conducted using a qualitative approach .The form of interviews used are in-depth to obtain a deep, open-ended explanation of the impact of Web 2.0 and user generated content on holiday decision-making. Adults with a family above the age of 30 are interviewed who prefer going on family holidays. Later the interviews are transcribed and analyzed and the interpretation was conducted. The study ends with limitations, marketing implication and future research scope.